Making the connection between health equity and sustainability - Shelton, Rachel C.; Hailemariam, Maji; Iwelunmor, Juliet (Frontiers in Public Health, 2023)
Sustainability and health inequities are key challenges in public health and healthcare. Research suggests that only about half of evidence-based interventions (EBIs) are sustained over time, and settings and populations experiencing systemic and structural barriers to health (e.g. poverty, racism, stigma and discrimination) experience even greater challenges to sustainability. In this article, we argue that an enhanced focus on sustainability in the field of implementation science is critical in order to maximize the long-term health benefits and broader societal impacts of EBIs for all populations and settings. From an equity perspective, a focus on sustainability is particularly critical to prioritize among population sub-groups that have not historically received the benefits of health-related EBIs. We discuss how a health equity framing is essential to sustaining EBIs in under-resourced communities, and requires moving away from a deficit mindset that focuses on why EBIs are challenging to sustain, to one that focuses more on identifying and nurturing existing assets within individuals and communities to increase the likelihood that EBIs are sustained. We conclude with a discussion of future directions as well as recommendations and resources (e.g. frameworks, tools) to advance and make progress towards sustainability from a health equity mindset, including: 1) Actively planning early for sustainability alongside key partners; 2) Tracking progress towards enhancing sustainability and being accountable in doing so equitably for all settings and populations; and 3) Focusing on both equity and engagement early and often throughout the research process and all implementation phases.